Manajemen Perencanaan Kurikulim Bahasa Arab - Assagaf, Muhammad Ridha (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to analyze the management of Arabic curriculum planning in Islamic educational institutions, focusing on need analysis, vision and mission formulation, curriculum design, implementation, and evaluation. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, observations, and document analysis, and analyzed using thematic methods. The findings revealed that Arabic curriculum management involves strategic stages to ensure comprehensive learning materials and student competency development. Challenges include limited technology-based learning resources and suboptimal evaluation of the affective domain. Teachers play a crucial role as innovators in the learning process. Overall, curriculum management has been well-executed but requires improvement, particularly in integrating technology and strengthening evaluation. This study concludes that effective management of Arabic curriculum planning supports education quality enhancement through structured and competency-based governance tailored to students’ and societal needs